Elevated serum levels of TNF‐α, IL‐6, and IL‐18 in chronic methamphetamine users. (25th August 2021) - Luo, Yayan; He, Hongbo; Ou, Yufen; Zhou, Yanling; Fan, Ni
Abstract: Objective: Chronic methamphetamine use causes aberrant changes in cytokines. Our aim was to analyze the serum levels of tumor necrosis factor α (TNF‐α), interleukin (IL)‐6, and IL‐18 in chronic methamphetamine users. Associations between cytokines levels with the demographic properties, methamphetamine use properties, and psychiatric symptoms in chronic methamphetamine users were also evaluated. Methods: Seventy‐eight chronic methamphetamine users who did not continue methamphetamine exposure since hospitalization and 64 healthy controls were enrolled. Serum levels of TNF‐α, IL‐6, and IL‐18 were detected using an enzyme‐linked immunosorbent assay. Psychopathological symptoms of chronic methamphetamine users were evaluated by the Positive and Negative Syndrome Scale, Beck Depression Inventory (BDI), and Beck Anxiety Inventory. Results: Serum levels of TNF‐α, IL‐6, and IL‐18 were significantly increased in methamphetamine users who did not continue methamphetamine exposure since hospital admission (average days since last methamphetamine use = 39.06 ± 7.48) when compared to those in controls. Serum IL‐6 levels showed significant positive associations with BDI score and current frequency of methamphetamine use in chronic methamphetamine users. Conclusions: Our results suggest that increased TNF‐α, IL‐6, and IL‐18 levels may have an important role in chronic methamphetamine use‐associated psychopathological symptoms.